A correlation‐based and spectrum‐aware admission control mechanism for multimedia streaming in cognitive radio sensor networks. (7th May 2015) - Hosseini, Elahe S.; Esmaeelzadeh, Vahid; Berangi, Reza; Akan, Ozgur B.
Summary: Bandwidth management and traffic control are critical issues to guarantee the quality of service in cognitive radio networks. This paper exploits a network load refinement approach to achieve the efficient resource utilization and provide the required quality of service. A connection admission control approach is introduced in cognitive radio multimedia sensor networks to provide the data transmission reliability and decrease jitter and packet end‐to‐end delay. In this approach, the admission of multimedia flows is controlled based on multimedia sensors' correlation information and traffic characteristics. We propose a problem, connection admission control optimization problem, to optimize the connection admission control operation. Furthermore, using a proposed weighting scheme according to the correlation of flows issued by multimedia sensors enables us to convert the connection admission control optimization problem to a binary integer‐programming problem. This problem is a kind of a Knapsack problem that is solved by a branch and bound method. Simulation results verify the proposed admission control method's effectiveness and demonstrate the benefits of admission control and traffic management in cognitive radio multimedia sensor networks. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A problem, connection admission control optimization problem, is proposed to optimize the connection admission control operation with event reliability cognitive radio channel constraints. Furthermore, using a proposed weighting scheme according to the correlation of flows issued by multimedia sensors enables us to convert this problem to a kind of a Knapsack problem that is solved by a branch and bound method. The simulation results demonstrate the benefits of admission control in cognitive radio multimedia sensor networks.